2023
DOI: 10.3390/ijms24043548
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Administration of Bevacizumab with Bee-Pollen Extract-Loaded Hybrid Protein Hydrogel NPs Is a Promising Targeted Strategy against Cancer Cells

Abstract: Bevacizumab (Bev) a humanized monoclonal antibody that fights vascular endothelial growth factor A (VEGF-A). It was the first specifically considered angiogenesis inhibitor and it has now become the normative first-line therapy for advanced non-small-cell lung cancer (NSCLC). In the current study, polyphenolic compounds were isolated from bee pollen (PCIBP) and encapsulated (EPCIBP) inside moieties of hybrid peptide–protein hydrogel nanoparticles in which bovine serum albumin (BSA) was combined with protamine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Similary our previous results con rmed the present nding that bioactive materials isolated from bee pollen have potential therapeutic effect on non small lung cancer celllines [44,45].…”
Section: Qrt-pcr Data Analysissupporting
confidence: 93%
“…Similary our previous results con rmed the present nding that bioactive materials isolated from bee pollen have potential therapeutic effect on non small lung cancer celllines [44,45].…”
Section: Qrt-pcr Data Analysissupporting
confidence: 93%
“…Furthermore, the combination therapy assay of BPENPs and the chemotherapeutic drug Avastin at their IC50 levels demonstrated a unique synergism, highlighting the therapeutic aspect of these polymeric nanoparticles for cancer therapy by blocking cancer-promoting cellular signaling and activating apoptotic pathways in cancer cells. Another study by Hanafy et al reported similar findings where administration of BPE encapsulated within hybrid hydrogel nanoparticles significantly improved the anti-cancer effectiveness of Bevacizumab against A549 and MCF-7 cell lines when used in combination [111]. Such findings are a strong impetus for using bee pollen nanoparticles in conjunction with chemotherapy to increase efficacy while reducing the required dose.…”
Section: Bee Pollen For Nanoparticle Developmentmentioning
confidence: 75%